Analisis Kepuasan Pengguna Market Place Terhadap Pengalaman Berbelanja Online: Studi Kasus Pada Aplikasi Shopee di Kalangan Konsumen Gen Z Di Purwakarta - Cica Nurhasanah; Dede Jajang Suryaman (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The rapid development of technology has encouraged the growth of online marketplaces as digital transaction platforms, one of which is Shopee. This study aims to determine the level of satisfaction among Generation Z consumers in Purwakarta regarding their shopping experience on Shopee and to analyze the influence of feature convenience and corporate image on consumer satisfaction. This research uses a quantitative method by distributing questionnaires to 53 respondents. The results of multiple linear regression analysis show that corporate image has a positive and significant effect on consumer satisfaction, with a coefficient value of 1.039 (t = 10.136; sig < 0.001). Meanwhile, feature convenience does not have a significant effect (t = -1.308; sig 0.200 > 0.05). Overall, both variables contribute 73.2% to consumer satisfaction (Adjusted R² = 0.732), while the remaining 26.8% is influenced by other factors outside the study. These findings indicate that corporate image is the most dominant factor in increasing satisfaction among Generation Z Shopee users.